Disappearing Tricks : Silent film, Houdini, and the New Magic of the Twentieth Century - Solomon, Matthew (Urbana, Chicago, IL : University of Illinois Press, 2010)
An anti-spiritualist medium : stage magic and the beginnings of cinema -- The death of magic? presentational performance and early film -- Behind the curtain : Méliès at the Théâtre Robert-Houdin -- Up-to-date magic : theatrical conjuring and the trick film -- Houdini's actuality magic : escaping the "ghost house" with moving pictures -- Lost in transition : sensational fiction and the limits of narrative integration -- Epilogue.
"Disappearing Tricks revisits the golden age of theatrical magic and silent film to reveal how professional magicians shaped the early history of cinema. While others have called upon magic as merely an evocative metaphor for the wonders of cinema, Matthew Solomon focuses on the work of the professional illusionists who actually made magic with moving pictures between 1895 and 1929."--BOOK JACKET.
boek
Keywords: Houdini